2018
DOI: 10.1253/circj.cj-18-0410
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-377 Inhibits Atherosclerosis by Regulating Triglyceride Metabolism Through the DNA Methyltransferase 1 in Apolipoprotein E-Knockout Mice

Abstract: It is concluded that miR-377 upregulates GPIHBP1 expression, increases the LPL binding to GPIHBP1, and reduces plasma triglyceride levels, likely through targeting DNMT1, inhibiting atherosclerosis in ApoE-KO mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…A previous study suggested that patients with hypertriglyceridemia had significantly lower miR-377 level compared with non-hypertriglyceridemic subjects and miR-377-3p might participate in regulation of triglyceride metabolism [11]. Hence, the down-regulation of miR-377-3p levels in AS mice might be related to high fat intake.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study suggested that patients with hypertriglyceridemia had significantly lower miR-377 level compared with non-hypertriglyceridemic subjects and miR-377-3p might participate in regulation of triglyceride metabolism [11]. Hence, the down-regulation of miR-377-3p levels in AS mice might be related to high fat intake.…”
Section: Discussionmentioning
confidence: 97%
“…MiR-377, which is located in chromosome region 14q32, is emerged to suppress tumors [7], oxidative stress and inflammation in ischemic hearts [8] and glomerular podocyte injury [9], and promote cardiac regenerative ability in stem cells after ischemia-reperfusion injury [10]. A previous report has shown that miR-377 reduced triglyceride levels in plasma and significantly decreased the area of aortic lesions in apolipoprotein E knockout (ApoE −/− ) models [11]. In addition, miR-377 can regulate inflammation and suppress the abnormal proliferation and migration of brain microvascular endothelial cells (ECs) [12].…”
Section: Introductionmentioning
confidence: 99%
“…miR-377: A recent study in rats reported that hepatic miR-377 expression was modulated by the consumption of distinct dietary lipids 138 , suggesting that altered miR-377 levels may affect the development of atherosclerosis. Supportingly, patients with aberrant elevated plasma levels of triglyceride, a risk factor for atherosclerosis, concomitantly display reduced circulating levels of miR-377 139 . Studies in Apoe-deficient mice demonstrated that exogenous addition of miR-377 suppressed plasma triglyceride levels in response to high-fat feeding and reduced aortic root atherogenesis, while conversely miR-377 antagomir administration accelerated lesion development 139 .…”
Section: Animal Studiesmentioning
confidence: 99%
“…Supportingly, patients with aberrant elevated plasma levels of triglyceride, a risk factor for atherosclerosis, concomitantly display reduced circulating levels of miR-377 139 . Studies in Apoe-deficient mice demonstrated that exogenous addition of miR-377 suppressed plasma triglyceride levels in response to high-fat feeding and reduced aortic root atherogenesis, while conversely miR-377 antagomir administration accelerated lesion development 139 . Mechanistic insight gained from studies in ECs proposed enhanced miR-377 levels suppress DNMT1 expression which permits LPL binding to ECs and subsequent hydrolysis of triglycerides and a reduction in their circulating levels 139 .…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation